German Moravian missionaries in the British colony of Victoria, Australia, 1848-1908 : influential strangers - Jensz, Felicity. (Studies in Christian Mission, 2010)
Focusing on the six decades that German Moravian missionaries worked in the British colony of Victoria, Australia, this book enriches understanding of colonial politics and the role of the non-British other in manipulating practice and policy in foreign realms. Central to the transnational nature of the book are questions of identity and of how individuals, and the organisations they worked for, can be seen as both colluders and opposers within nation-state borders and politics. It analyses the ways in which the Moravian missionaries navigated competing agendas within the colonial setting, especially those that impacted on their sense of personal vocation, their practices of conversion, and their understandings of the indigenous non-Christian peoples in the settler society of Victoria.